Pursuing Happiness In Modern Era; Study On Hamka’s Perspective - Maria Ulfa; Erva Dewi Arqomi Puspita (Tasfiyah: Jurnal Pemikiran Islam, 2020)
This paper aims to examine Haji Abdul Malik Karim Amrullah’s thought on happiness. He was known as Hamka, a multitalented Indonesian scholar. His thoughts influence many disciplines such as politics, literature, cultural history, and teachings of the renewal of Neo-Sufism. Hamka had found the relevance of the concept toward modern life. According to him, all people around the world have to admit that religion is the only way to solve all problems they have in this era and it is also the only way to reach happiness in their life. Through religion, the people would be able to manage their reason or mind and their attitude to receive any knowledge easily. So that, the people can achieve the happiness in any conditions.